2CUL Slavic: The View So Far. (3rd April 2017) - Davis, Robert
ABSTRACT: In fall 2016, the Columbia-Cornell collaboration in the area of Slavic & East European resource coordination and sharing celebrated its sixth year. The author reviews particulars of the development, implementation, and function of this program as well as some of the challenges that face such cross-institutional efforts.